(untitled) (Journal of the College of Basic Education, 2022)
Educational technologies in general, and the educational computer in particular, are considered an essential pillar of the educational-learning process and an integral part of the comprehensive educational system. And communication and its developments, in order to achieve its goals in accordance with the educational / learning system